HUBUNGAN ANTARA AKTIVITAS MENGGAMBAR PADA MEDIA LAYANGAN DENGAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI DI KELOMPOK B RA AL-PATWA CICUKANG BANDUNG - Eli Khoerussaadah; Hilman Mangkuwibawa; Syam’iyah Syam’iyah (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This research was motivated by the difference between the high drawing activity and low fine motor skills in early childhood in group B RA Al-Patwa Cicukang Bandung. This can be seen from the child’s response when doing drawing activities that are so enthusiastic. Meanwhile his fine motor skills are still not well developed. This can be seen when children do pre-writing activities, some children still have difficulty moving their hands flexibly. This study aims to determine: 1) Drawing activities on kite media; 2) Fine motor skills in early childhood; 3) The relationship between drawing activity on kite media and fine motor skills of early childhood in group B RA Al-Patwa Cicukang Bandung. This study also used a quantitative approach with the correlation method, with the research subjects being children in group B RA Al-Patwa Cicukang Bandung with a population of 15 children. Data collection techniques using observation and dokumentation. The result obtained in drawing activities in early childhood obtained an average value of 77. Meanwhile, fine motor skills obtained an average value of 80, both of wich are intended to develop as expected (BSH). Drawing activities on kite media also have an influence on fine motor skills of early childhood by 86,5%